Prediction and characterization of the linear IgE epitopes for the major soybean allergen β-conglycinin using immunoinformatics tools - Sun, Xiulan; Shan, Xiaohong; Yan, Zihe; Zhang, Yinzhi; Guan, Lu (Food and chemical toxicology, 2013)
► Three immunoinformatics tools were used to predict the potential epitopes. ► Dot-blot inhibition using sera from soybean allergic subjects confirm the epitopes. ► 11/15 of the predicted epitopes can react with 3/5 human sera. ► All the predicted epitopes can react with at least one of the human sera. ► One of epitopes can react with all of human sera. The α subunit of β-conglycinin is a major allergen in soybean. The objective of this study was to predict and identify the linear immunoglobulin (Ig)E epitopes of the soybean α subunit of β-conglycinin. Three immunoinformatics tools were used to predict the potential epitopes and were confirmed by dot-blot inhibition using sera from soybean allergic subjects. As a result, 15 peptides were predicted and assembled by solid-phase synthesis. Eleven epitopes were identified by the dot-blot inhibition test. Moreover, peptide 3 had IgE binding capability with all sera(5/5) tested, while peptide 1, 4, 6, 8 and12 could bind to 4/5 of the sera samples. Secondary structure prediction of peptide 3 and circular dichroism test validated that the structure of peptide 3 was a random coil.